Rupture, evolution, and continuity : the Shandong Peninsula in East Asian maritime history during the Yuan-Ming Transition - Ma, Guang (East Asian economic and socio-cultural studies. East Asian maritime history ;, 2021)
"While previous scholars have paid much attention to the maritime history of Guangdong, Fujian, and Zhejiang in southern China, by contrast, there are no monographs or articles focusing on maritime history of Shandong in northern China in Western scholarship. However, as a matter of fact, Shandong played a significant role in East Asian maritime history. This book attempts to break through the 'Southeast China-centric' framework by focusing attention on the Shandong Peninsula during the Yuan-Ming transition (late thirteenth to early fifteenth centuries). Many scholars have argued that there was rupture between the two dynasties in politics, society, and culture, or have argued the opposite from the perspective of land-centric history. By placing Shandong maritime history into a supra-regional, global historical context, the author's study challenges the Southeast China centrism, the terra-centric model and various traditional views. Ma argues that on the one hand, there were obvious 'ruptures' of maritime policy and maritime trade from the Yuan to the Ming dynasties, and on the other hand, some things, such as official sea transportation, continued from Yuan to Ming times. More importantly, although the function of the Shandong Peninsula changed from being primarily an important commercial entrepôt in the Yuan to being a crucial military base during Ming times, it is worth mentioning that it was a process extending over several decades, rather than a simple rupture."--